The Impact of the COVID-19 Pandemic on Surgical Mask Prices at Klinik Pratama An-Nur Bandung - Neng Riny Rahmawati; Marissa Putri A (JOURNAL EKONOMI, KEUANGAN, PERBANKAN DAN AKUNTANSI SYARIAH, 2025)
The COVID-19 pandemic generated an unprecedented demand shock for personal protective equipment worldwide, with surgical masks at its epicentre. This study examines the magnitude and dynamics of surgical mask price volatility at Klinik Pratama An-Nur Bandung during the period December 2019 to May 2020, employing a quantitative descriptive approach supported by simple linear regression analysis. Primary data were drawn from procurement records (Bahan Medis Habis Pakai) of the clinic across six consecutive months. The findings reveal a 2,150% price escalation from IDR 20,000 to IDR 450,000 per box within five months of the first confirmed COVID-19 case in Indonesia (March 2020). Regression analysis confirms a statistically significant positive relationship between pandemic intensity and surgical mask prices (β = 0.667, t = 3.801, p = .001). The study situates this price surge within the broader literature on supply-demand asymmetry during health crises, arguing that pre-pandemic procurement infrastructure and supplier diversification are the primary structural vulnerabilities. These findings carry direct implications for healthcare facility procurement resilience in low- and middle-income countries.